A study to evaluate and compare the outcomes of endoscope versus microscope assisted myringoplasty - Babu, K. Sharath; Shankar, R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: In microscope assisted middle ear procedures surgeons can only observe the parts of the tympanic cavity, the hidden areas, such as the facial recess and sinus tympani, would not be visualised which needs to be exposed for performing tympanoplasty. The aim of the study was to compare the outcomes of microscope versus endoscope assisted myringoplasties in terms of duration of the procedure, graft take up, improvement in hearing and incidence of any complications. Methods: A prospective comparative study was conducted for a period of one year. A total of 72 patients with CSOM were randomised into two groups of 36 each. Group A patients (n=36) underwent traditional myringoplasty under a microscope and group B patients (n=36) endoscopic assisted myringoplasty was performed. Post-operatively all the patients were followed up for a period of one year. During the follow-up period patients were assessed for the graft take up, hearing improvement, incidence of complications and recurrence rate between the two groups. Results: Successful graft uptake was observed in 88.8% among patients underwent microscope assisted myringoplasty and it was 94.4% in endoscopic assisted myringoplasty. The mean duration of surgery was 123 mins in microscopic assisted group compared to 92 mins in endoscopic assisted group and the difference was found to be statistically significant. Similarly, the cosmetic results and the post-operative pain were more favorable for endoscopic assisted group than microscopic assisted group and the difference was found to be statistically significant. Conclusions: Enoscopic assisted procedure could be considered as a better alternative for microscopic assisted myringoplasty.